Breast Cancer Screening in Inner City and County Populations: A Tale of Two Centers. Issue 6 (June 2021) - Castaldi, Maria; Smiley, Abbas; Butler, Jonathan; Latifi, Rifat
Background: New York's statewide "Get Screened, No Excuses" campaign has been one of the nation's most aggressive actions to improve access to breast cancer screening. Inner city and suburban county medical centers' initiatives were studied to compare outcomes of breast cancer screening and factors that influence access to care. Methods: Women delinquent in breast cancer screening one year or greater were offered patient navigator services to aid in timely breast cancer screening. Time-to-event completion rates among different stages of breast cancer screening stages in City and County women were compared. Time-to-event completion rates among different stages of breast cancer screening stages. Results: 2505 women aged ≥40 years accepted PN services. Mean (SD) age of patients was 56.2 (10) years. The mean (SD) age of those who completed breast screening vs. those who did not was 56.8 (10) and 52.5 (.9) years, respectively ( P < .01). The rates of screening completion during physical examination, mammography and biopsy stages were 74%, 78% and 100% in City vs. 98%, 85% and 100% in County, respectively ( P < .001). Screening phase was the significant predictor of time to completion for breast cancer screening in Cox regression analysis. Over 85% of women completed the breast cancer screening, 74% in City and 97.6% in County ( P < .001). Discussion: Screening phase is an important predictor of time-to complete breast cancer screening. Center location served as the effect modifier of the relationship. The rate of completing the screening was significantly higher and faster among Suburban County compared to Inner City women.